Selection for cheating across disparate environments in the legume‐rhizobium mutualism - Stephanie S. Porter; Ellen L. Simms (Ecology Letters, 2014)
The primary dilemma in evolutionarily stable mutualisms is that natural selection for cheating could overwhelm selection for cooperation. Cheating need not entail parasitism; selection favours cheating as a quantitative trait whenever less‐cooperative partners are more fit than more‐cooperative partners. Mutualisms might be stabilised by mechanisms that direct benefits to more‐cooperative individuals, which counter selection for cheating; however, empirical evidence that natural selection favours cheating in mutualisms is sparse. We measured selection on cheating in single‐partner pairings of wild legume and rhizobium lineages, which prevented legume choice. Across contrasting environments, selection consistently favoured cheating by rhizobia, but did not favour legumes that provided less benefit to rhizobium partners. This is the first simultaneous measurement of selection on cheating across both host and symbiont lineages from a natural population. We empirically confirm selection for cheating as a source of antagonistic coevolutionary pressure in mutualism and a biological dilemma for models of cooperation.

Precision of host sanctions in the fig tree–fig wasp mutualism: consequences for uncooperative symbionts - K. Charlotte Jandér; Edward Allen Herre; Ellen L. Simms (Ecology Letters, 2012)
Host sanctions that reduce the relative fitness of uncooperative symbionts provide a mechanism that can limit cheating and thus stabilise mutualisms over evolutionary timescales. Sanctions have been demonstrated empirically in several mutualisms. However, if multiple individual symbionts interact with each host, the precision with which individual cheating symbionts are targeted by host sanctions is critical to their short‐ and long‐term effectiveness. No previous empirical study has directly addressed this issue. Here, we report the precision of host sanctions in the mutualism between fig trees and their pollinating wasps. Using field experiments and molecular parentage analyses, we show that sanctions in Ficus nymphaeifolia act at the level of entire figs (syconia), not at the level of the individual flowers within. Such fig‐level sanctions allow uncooperative wasps, which do not bring pollen, to avoid sanctions in figs to which other wasps bring pollen. We discuss the relevance of sanction precision to other mutualisms.

Transcriptomic insights into mechanisms of symbiotic cooperation - Ellen L. Simms; Stephanie S. Porter (Molecular Ecology, 2012)
Intraspecific genetic variation can affect community structure and ecosystem processes (Bolnick et al . 2011). It can also influence phenotypic expression by genotypes within other species to produce genotype‐by‐genotype ( G × G ) interaction (Falconer & Mackay 1996). Evolution of one species drives correlated evolution of others when it causes G × G for fitness (Thompson 2005). However, the mechanisms by which species interact also influence evolutionary outcomes (Kummel & Salant 2006; Golubski & Klausmeier 2010; Akçay & Simms 2011; Grman et al . 2012). To identify genes and putative functional mechanisms underlying G × G interactions, Heath et al . (2012) analysed natural variation in the symbiotic transcriptome of the mutualistic nutritional symbiosis between a legume host M edicago truncatula and the facultative endosymbiotic rhizobium S inorhizobium meliloti . Using twelve microarrays, the authors simultaneously measured host and symbiont gene expression in root nodules from four factorial pairings of host and symbiont genotypes that produced G × G in host fitness (Fig. 1, upper panel). Rhizobium gene expression was influenced by rhizobium and plant genotype and the G × G interaction (Fig. 1, lower panel), whereas plant gene expression was influenced primarily by plant genotype. The authors identified rhizobium genes that might contribute to G × G in host plant fitness. Heath et al . (2012) have moved beyond the constraints of single organism analysis towards a more realistic understanding of plants and bacteria as organisms inextricably linked with symbioses that affect even basic patterns of gene expression.

No evolution of increased competitive ability or decreased allocation to defense in Melaleuca quinquenervia since release from natural enemies - Steven J. Franks; Paul D. Pratt; F. Allen Dray; Ellen L. Simms (Biological Invasions, 2008)

Nickel hyperaccumulation as an anti-herbivore trait: considering the role of tolerance to damage - Martha Palomino; Peter G. Kennedy; Ellen L. Simms (Plant and Soil, 2007)

Epistasis and genotype-environment interaction for quantitative trait loci affecting flowering time in Arabidopsis thaliana - Thomas E. Juenger; Sunak Sen; Kirk A. Stowe; Ellen L. Simms (Genetica, 2005)

Genetic Variation and Relationships of Constitutive and Herbivore-Induced Glucosinolates, Trypsin Inhibitors, and Herbivore Resistance in Brassica rapa - Donald F. Cipollini; Jeremiah W. Busch; Kirk A. Stowe; Ellen L. Simms; Joy Bergelson (Journal of Chemical Ecology, 2003)

The relative advantages of plasticity and fixity in different environments: when is it good for a plant to adjust? - Peter Alpert; Ellen L. Simms (Evolutionary Ecology, 2002)

Defining tolerance as a norm of reaction - Ellen L. Simms (Evolutionary Ecology, 2000)

Will plant vigor and tolerance be genetically correlated? Effects of intrinsic growth rate and self-limitation on regrowth - Arthur E. Weis; Ellen L. Simms; Michael E. Hochberg (Evolutionary Ecology, 2000)

Effect of seed predation on seed bank size and seedling recruitment of bush lupine ( Lupinus arboreus ) - John L. Maron; Ellen L. Simms (Oecologia, 1997)